Postnatal phenotype according to prenatal ultrasound features of Noonan syndrome: a retrospective study of 28 cases. (24th January 2013) - Gaudineau, A.; Doray, B.; Schaefer, E.; Sananès, N.; Fritz, G.; Kohler, M.; Alembik, Y.; Viville, B.; Favre, R.; Langer, B.
ABSTRACT Objective Noonan syndrome is a frequent genetic disorder with autosomal dominant transmission. Classically, it combines postnatal growth restriction with dysmorphic and malformation syndromes that vary widely in expressivity. Lymphatic dysplasia induced during the embryonic stage might interfere with tissue migration. Our hypothesis is that the earlier the edema, the more severe postnatal phenotype. Method This retrospective study analyzed data from all 32 cases of Noonan syndrome diagnosed in the Medical Genetics Department of Hautepierre Hospital in Strasbourg, France, between 1995 and 2011. The postnatal evolution of Noonan syndrome was compared according to the presence of at least one prenatal ultrasound feature of lymphatic dysplasia. Results The most frequent prenatal ultrasound features found were increased nuchal translucency, cystic hygroma and polyhydramnios; their global prevalence was 46.4%. The presence of these features was not significantly associated with the postnatal phenotype of Noonan syndrome. Conclusion The results of our study indicate that prenatal ultrasound features of lymphatic dysplasia do not predict an unfavorable postnatal prognosis for Noonan syndrome. © 2013 John Wiley & Sons, Ltd.